DIFFERENT TYPES OF GINGIVAL SHADES USED IN FABRICATING AN AESTHETIC FIXED PARTIAL DENTURE - EVG, Karthik; Kommi, Venkatesh; TN, Uma Maheshwari (International Journal of Psychosocial Rehabilitation, 2019)
A heavy global burden of periodontal disease can have an undeniable negative. Replacing the partially edentulous area in the anterior region can be challenging in achieving an optimal aesthetic result. In the field of dentistry, its superior basis for achieving aesthetics and to replace and replicate the appearance of teeth to mimic nature to its closest sense and form.The aim of the study is to check the frequency of gingival shades used in the fabrication of fixed partial denture.The current study is an institutional based retrospective study performed over a review of 49832 cases.The results obtained shows the frequency ranges of gingival shades used in a fixed partial denture with gingival ceramics.Within the limitations of the study, The most common type of shade used was G2 and the most common gender undergoing treatment were male subjects.